(untitled) (Economic studies journal, 2023)
This study aims to assess the historical evolvement of entrepreneurship and innovation concepts in Libya. Also, it aims to investigate the entrepreneurship and innovation culture in the Libyan higher education institutions in six dimensions. Namely: academic staff, curricula, teaching methodology, administrative organization, support research projects, and the attitudes of academic staff toward this field in 2021. With the help of a descriptive approach (5-point Likert scale), findings revealed that the studied sample has many weaknesses in the field of entrepreneurship and innovation, particularly in the first five dimensions. While the only partially positive point was the academics’ attitudes towards the entrepreneurship and innovation field dimension. This study provides valuable implications and suggestions for academics and policymakers.